Exploration and Inventory of Ethnobotanical Knowledge of Medicinal Plants in Ternate: Tracing the Traditional Pharmacy Heritage of the Spice Islands - Lina Elfita; Hijria Abd Gani; Ismiarni Komala (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
The ethnobotanical wisdom of the Ternate community represents a rich heritage of traditional healing practices that are deeply rooted in the interaction between people and nature. However, the modernization of the healthcare system and cultural shifts have increasingly threatened the continuity of this indigenous knowledge. This study aimed to explore and inventory the ethnobotanical knowledge of medicinal plants traditionally used in the Ternate region as part of an effort to preserve the traditional pharmacy legacy of the Spice Islands. Data were collected through field-observations, semi-structured interviews with traditional healers, local residents, and plant specimen documentation. A purposive sample of 29 traditional healers was recruited for this study, based on their presumed expertise in medicinal plant knowledge. The study identified 70 medicinal plant species belonging to 40 families, which are empirically used to treat common ailments such as fever, digestive disorders, wounds, insomnia, diabetes mellitus, and urinary stones. Leaves were the most frequently used plant part (approximately 64%) followed by roots and barks, with decocting being the dominant preparation method. Several endemic species have demonstrated pharmacological potential, consistent with findings in contemporary scientific literature, indicating promising opportunities for bioprospecting. This research highlights that preserving ethnobotanical knowledge is not merely a cultural duty but also a scientific imperative for sustainable natural product development rooted in Ternate’s local wisdom.